Draft Genome Sequence of the Rumen Methanogen Methanobrevibacter olleyae YLM1 - Kelly, William J. (Genome Announc, 2016)
Methanobrevibacter olleyae YLM1 is a hydrogenotrophic methanogen, isolated from the rumen of a lamb. Its genome has been sequenced to provide information on the genomic diversity of rumen methanogens and support the development of approaches to reduce methane formation by ruminants.